SUDUT PANDANG SINEMATIK FILM â€œPRIDE AND PREJUDICEâ€ TAHUN 2005 DENGAN VERSI SERIAL TELEVISI TAHUN 1995 - Tarmawan, Irwan; Amalina, Rima Nur (Universitas Komputer Indonesia, 2019)
Film is communication and entertainment media comprising artistic and aesthetic elements. The source of stories in the film can be inspired by various sources, one of them is novel. Pride and Prejudice is one of Jane Austenâ€™s works in which its stories have been adapted in various artworks, such as film. Popular adaptation of Pride and Prejudice with similar title is the feature length film version published in 2005 and tv serial published in 1995. Film has two main elements of film making, namely: narrative and cinematic elements. Both elements related to each other for create cinematic point of view and aesthetic film.